An exploratory study of Muslim friendly hospitality services in Japan - Yumna, Hasbullah (2018)
Japan is becoming a more popular tourist destination among Muslims. Furthermore, the nation is preparing itself to host the Tokyo Olympics in 2020. Due to these reasons, both the Japanese government and business communities are eager to introduce halal products (primarily food and beverages) and services mainly in hotels and restaurants. All of these elements are important to attract Muslim tourists to visit Japan. This research revealed the perceptions from travel agencies in Malaysia and Japan towards the development of Muslim Friendly Hospitality Services (MFHS) in Japan. Furthermore, this research attempted to suggest some improvements in the guideline of Muslim Friendly Hospitality Services: MS 2610:2015 to fit within the Japanese context. This research revealed the key issues and challenges that Japanese travel agencies are facing in the halal and MFSH tourism. The research methodology used face-to-face interviews to collect primary data in understanding the underpinning issues. Research informants were five managers from the travel agencies in Malaysia and Japan. The Malaysian travel agencies provide tourism services to Japan for Malaysian tourist. On the other hand, the Japanese travel agencies focus on providing Muslim Friendly Hospitality Services to Muslim tourists. The data were collected and analysed using thematic analysis. Using the research findings, some improvements of the MS 2610:2015 were suggested to adapt to the context of Japan in managing Muslim Friendly Hospitality Services. Hence, with this research, the implementation of an improved version of the guidelines of Muslim Friendly Hospitality Services in Japan should be acceptable to both the practitioners and customers which can serve as an example for other non-Muslim countries.